Utilization of Barley in the Development of Fiber Enriched Chevon Cutlets - Singh, Pramod Kumar; Kumar, Sunil; Bhat, Z. F.; Kumar, Pavan (Journal of Meat Science, 2014)
A study was conducted to evaluate the possibility of utilization of barley as a source of fiber in the development of fiber-enriched designer chevon cutlets. Three levels of barley flour viz. 2, 4 and 6 percent were incorporated replacing lean meat in the formulation. The products developed were assessed for various physico-chemical, sensory, texture and colour parameters. pH, crude fiber, ash content, texture parameters like hardness, adhesiveness, springiness, cohesiveness, chewiness, gumminess and product redness value showed significant (P<0.05) increasing trend whereas flavor, juiciness and overall acceptability decreased significantly (P<0.05) with increasing levels of incorporation. Based on various physico-chemical and sensory parameters, chevon cutlets containing 4 percent barley flour were optimized as best.